2011
DOI: 10.1002/app.35276
|View full text |Cite
|
Sign up to set email alerts
|

Tensile modulus modeling of carbon black/polycarbonate, carbon nanotube/polycarbonate, and exfoliated graphite nanoplatelet/polycarbonate composites

Abstract: Conductive fillers are often added to thermoplastic polymers to increase the resulting composite's electrical conductivity (EC) which would enable them to be used in electrostatic dissipative and semiconductive applications. The resulting composite also exhibits increased tensile modulus. The filler aspect ratio plays an important role in modeling composite EC, and tensile modulus. It is difficult to measure the filler aspect ratio after the manufacturing process (often extrusion followed by injection molding)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
(122 reference statements)
0
9
0
Order By: Relevance
“…For this work, the electrical resistivity was measured using the four‐point probe method. Figure shows the volume resistivity of various types of polymer/nanofiller composites . Because the electrical properties of the composites reported herein were better than those reported for other composites, it was expected that they would also have good EMI SE.…”
Section: Resultsmentioning
confidence: 84%
“…For this work, the electrical resistivity was measured using the four‐point probe method. Figure shows the volume resistivity of various types of polymer/nanofiller composites . Because the electrical properties of the composites reported herein were better than those reported for other composites, it was expected that they would also have good EMI SE.…”
Section: Resultsmentioning
confidence: 84%
“…Last decade, many scientific efforts have been made for the synthesis of multifunctional polymer nanocomposites that take advantage of the unique mechanical and structural properties of new graphitic forms as graphene (GNPs) and multiwall carbon nanotubes (MWCNTs) [1][2][3][4][5]. There are a lot of studies on carbon composites based on a wide range of polymers, reported in the literature as polycarbonate [6], nylon [7], poly(methyl methacrylate) [8], epoxy resin [9], poly(vinyl alcohol) [10], polystyrene [11], polycaprolactone [12], poly(propylene) [13], and poly(lactic acid) [14,15]. One of the main parameters that influences the composite properties is the distribution/dispersion of the carbon nanofillers in conjunction with their weight percentage loading in the polymer matrix [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been considered extremely challenging to commercialize advanced products fabricated with graphene due to inability in mass production of high-quality graphene at low cost. Recently, graphene nano-platelets (GnPs) have been recognized as an inexpensive alternative to graphene due to its possibility of mass production at low cost [10,11]. GnPs are layered graphene nano-crystals in the structure of platelets stacked by van der Waal's forces [12].…”
Section: Introductionmentioning
confidence: 99%